Effectiveness of Trainer-Kit in the Learning Process in Vocational Education - Hansi Effendi; Deris Oktageri; Herlin Setyawan; Wiwinda Aulia (Universitas Pendidikan Ganesha, 2025)
Vocational learning processes are still dominated by one-way and theoretical teaching, thereby limiting the development of practical competencies and impacting learning outcomes. Trainer kits are used as learning media to support practice and reduce the abstraction of technical concepts. However, previous research findings on their effectiveness have been inconsistent due to contextual limitations, small samples, and variations in research design. This study aims to analyze comprehensively the effectiveness of trainer kit implementation in vocational education through a meta-analysis approach. A total of 436 articles were initially screened from Scopus and Google Scholar databases, and 22 eligible studies involving 24 independent samples were selected based on inclusion criteria. Data analysis employed the random-effects Hedges’ model with the PRISMA procedure, focusing on effect sizes derived from post-test results of experimental and control groups. The meta-analysis revealed an average effect size of 2.44, categorized as large, confirming the significant positive impact of trainer kits on cognitive, psychomotor, and affective learning domains. The findings demonstrate that trainer kits not only improve academic achievement but also enhance learning motivation and creative thinking skills. This study concludes that trainer kits are highly effective instructional media in vocational education and emphasizes the importance of their systematic integration into teaching practices. The results provide evidence-based implications for educators and policymakers to design innovative learning strategies and develop vocational curricula aligned with industry demands and 21st-century skills.